Visual Representation of Photography on the Cover of Fiction Novels - Arsita, Adya (Universitas Pasundan, 2024)
As a visual sign, photography is considered to be the right mediun to represent an object with all its resemblance with the reality. The reality embedded in a photography is in line with the reliability of its audience who adhere to